Pre-lithiated silicon-carbon composite material, anode including same, and method of making composite material

By applying metal oxide coating and preliminary alloy treatment on the surface of lithium silicon carbon composite materials, the chemical instability and lithium ion loss of lithium ion during the electrolyte filling process is solved, and higher chemical stability is achieved and battery capacity.

CN119318026APending Publication Date: 2025-01-14SELFOSS GRP GMBH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380042095.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-14
Filing Date
2023-04-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to react with environmental compounds during the electrolyte filling process, resulting in chemical instability and lithium ion losses, especially when the SEI layer is formed, affecting battery capacity and life.

Method used

The lithium silicon carbon composite material using porous carbon scaffolds is applied to the surface by chemical vapor deposition and other methods to form a surface coating to improve chemical and mechanical stability, and lithium and silicon are introduced through solution permeation to form Preliminary alloy reduces the formation of the SEI layer.

Benefits of technology

The chemical stability of lithium-silicon carbon composite material is significantly improved, reducing the loss of lithium ions due to the SEI layer during the first cycle, extending battery life and improving battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318026A_ABST
    Figure CN119318026A_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium-silicon-carbon composite material, in particular a lithium-silicon-carbon composite material formed as a surface coating, comprising a porous carbon scaffold comprising micropores and mesopores and having a total pore volume of not less than 0.5 cm3 / g; a silicon content of from 30% to 70% (including 30% and 70%); a lithium content of from 2% to 20% (including 2% and 20%); and a first surface coating at least partially applied, the first surface coating forming a surface coating on a surface region of the lithium silicon carbon composite, the first surface coating comprising one or more elements of Li, B, Al, Si, P, Ti, Zr, Nb and / or W.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a surface-coated lithium silicon carbon composite material, which comprises a porous carbon support, wherein the porous carbon support comprises micropores and mesopores having a pore volume. In addition, the present disclosure relates to a method for manufacturing the surface-coated lithium silicon carbon composite material, an anode electrode and an electrochemical energy storage device. Background Art

[0002] Lithium-ion batteries are widely used and provide stored energy for different components. In particular, in electric vehicles and hybrid vehicles, such lithium-ion batteries provide electrical energy for vehicle components and the powertrain. In such applications, it is highly desirable to obtain a longer electric driving range, which can be achieved by increasing the capacity of the battery. The capacity of the battery can be increased by increasing the surface area of ​​the electrode. This can be achieved by more complex surface structures. There are known methods for coating at least one current collector of the anode with silicon carbon to increase the area of ​​reversible lithium insertion and the number of lithium ions involved in the charging and discharging process. Such complex surface structures and coatings may easily react chemically with compounds in the environment (for example, during the manufacture of lithium-ion batteries). In particular, during the filling process of the electrolyte of the lithium-ion battery, parts of the anode and its surface structure may be accidentally exposed to harmful substances (for example, oxidizing substances).

[0003] Furthermore, after a large number of cycles, lithium-ion batteries are still susceptible to capacity loss due to the formation of a solid electrolyte interphase layer (SEI layer). This SEI layer is usually formed during the charge and discharge cycles of lithium-ion batteries due to the reduction of organic solvents and anions on the electrode surface. The formation of the relevant part of the SEI layer occurs during the first charge and discharge cycle. Summary of the invention

[0004] The object of the present disclosure is to provide a lithium silicon carbon composite material and a method for producing a lithium silicon carbon composite material, which has improved chemical stability and reduces lithium loss caused by the formation of an SEI layer in the first cycle of an electrochemical device. This object is achieved by the subject matter of the independent claim. Further improvements to the subject matter of the independent claim are provided in the dependent claims.

[0005] According to one aspect of the present disclosure, a lithium silicon carbon composite material is provided. The lithium silicon carbon composite material can be formed as a surface-coated lithium silicon carbon composite material or a surface-coated lithium alloy silicon carbon composite material.

[0006] This lithium silicon carbon composite material can be used in anode electrodes and thus in electrochemical energy storage devices such as lithium ion batteries or lithium ion batteries.

[0007] The lithium silicon carbon composite material comprises a porous carbon scaffold having micropores and mesopores and a total pore volume greater than 0.5 cm 3 / g.

[0008] In addition, the porous carbon scaffold of the lithium silicon carbon composite material can contain a plurality of particles for additionally adjusting its chemical and mechanical properties. Providing additional particles inside the porous carbon scaffold of the lithium silicon carbon composite material can control the dynamics of lithium ions inside the lithium silicon carbon composite material.

[0009] The lithium silicon carbon composite material contains a silicon content between 30% and 70% (including 30% and 70%). In addition, a lithium content of 2% to 20% (including 2% and 20%) is incorporated into the lithium silicon carbon composite material. Therefore, the lithium silicon carbon composite material is provided in a pre-lithiation form. The silicon content and the lithium content can be defined relative to the weight / mass or volume of the entire lithium silicon carbon composite material.

[0010] In addition, the lithium silicon carbon composite material comprises an at least partially applied first surface coating, which forms a surface coating on the surface area of ​​the lithium silicon carbon composite. The at least partially applied first surface coating comprises one or more elements of Li, B, Al, Si, P, Ti, Zr, Nb and / or W.

[0011] In another aspect of the present invention, an anode electrode is provided, which comprises a surface-coated silicon-carbon material. The anode electrode preferably comprises a current collector, such as a metal foil. The lithium silicon-carbon composite material can be provided on one or both sides of the current collector to improve the electrical properties of the anode electrode. The surface-coated silicon-carbon material is preferably in a pre-lithiation form, and thus serves as a surface-coated lithium silicon-carbon material.

[0012] For example, the lithium silicon carbon composite may include at least one surface coating on a surface area that is not in contact with the current collector of the anode electrode.

[0013] By providing at least one surface coating (e.g., a first surface coating), the chemical and mechanical stability of the surface-coated lithium silicon carbon composite material and thus the chemical and mechanical stability of the anode electrode having such a material is improved. In particular, the surface coating can be applied by chemical vapor deposition (e.g., an atomic layer deposition process). Such a surface coating can also be applied to lithium silicon carbon composite materials having complex or uneven surface geometries.

[0014] Since lithium is introduced into the surface-coated lithium silicon carbon composite material, the formation of the SEI layer during the first charge and discharge cycle of the anode electrode having such a material can be prevented or minimized. The SEI layer is generally formed due to the reduction of organic solvents and anions on the surface of the anode electrode during the charge and discharge cycles of the electrochemical cell. Since such organic solvents and anions are not present in the pre-lithiated composite material, the formation of the SEI layer can be minimized.

[0015] When the at least partially applied first surface coating forms a layer with a thickness of 0.1 nm to 1 μm, lithium ions for reversible lithium insertion can bypass the first surface coating without significantly reducing the corresponding kinetics.

[0016] According to another embodiment, the first surface coating comprises a metal oxide from at least one or more of the elements B, Al, Si, Zr, Nb and / or W. For example, suitable metal oxides may be formed as Al2O3 and / or LiAlO2.

[0017] In another embodiment, suitable metal oxides may be formed as ZrO2 or / and Li2ZrO3, or a mixture of Al2O3, ZrO2, and mixed lithium aluminum oxide and lithium zirconium oxide.

[0018] In another embodiment, the first surface coating contains a metal oxide formed from Li in addition to Al2O3.

[0019] A suitable surface coating may be applied by an atomic layer deposition (ALD) process of trimethylaluminum and water or oxygen at a temperature between 100°C and 450°C (followed by two or more ALD cycles), followed by the optional chemical reaction of the resulting aluminum oxide and aluminum hydroxide with a lithium compound (such as Li-N(SiMe3)2) to form a lithiated metal oxide. Such a coating may also be applied in combination with thermal exposure and / or a catalyst. In another embodiment, the surface coating may be applied by mixing a metal oxide compound (Al2O3, Zr(OH)4, ZrO(OH)2) with a lithium compound, followed by a thermal treatment step at a temperature above 200°C.

[0020] In another embodiment, the first surface coating covers at least 50% of the surface area of ​​the lithium silicon carbon composite material. Thus, most of the surface area of ​​the lithium silicon carbon composite material can be protected by the first surface coating. The surface area of ​​the lithium silicon carbon composite material is defined as the entire surface area of ​​its final form applied to the anode electrode. Thus, all or most of the surface of the lithium silicon carbon composite material that is not in contact with the current collector foil of the anode electrode can have a surface coating.

[0021] The surface coating of the lithium silicon carbon composite material may include multiple surface coatings, which may also at least partially cover the available surface area of ​​the lithium silicon carbon composite material. Different surface coatings may at least partially overlap each other.

[0022] When the surface area of ​​the lithium silicon carbon composite material is at least partially covered by the first surface coating and at least partially covered by the second surface coating, the lithium silicon carbon composite material can have additional protection. Preferably, the second surface coating is at least partially applied on top of the first surface coating and / or next to the first surface coating. The second surface coating can provide additional control of the chemical and mechanical stability of the lithium silicon carbon composite material.

[0023] Based on one embodiment of the lithium silicon carbon composite material, the second surface coating is formed as a carbon coating. When the lithium silicon carbon composite material is used in the electrode, this second surface coating can cause the resistance of the lithium silicon carbon composite material in the transition region between the second surface coating and the current collector or metal to be reduced. In addition, this second surface coating can increase the conductivity within the lithium silicon carbon composite material layer. In another embodiment, an additional step can be applied to further passivate the surface area or the lithium silicon carbon composite material by flushing with a dry atmosphere (O2, N2 or a mixture thereof) above the lithium silicon carbon composite material at an elevated temperature between 120°C and 250°C. This process helps to improve the processability of the water-based binder solution, especially the formation of H2 can be avoided.

[0024] In another embodiment of the lithium silicon carbon composite material, the lithium silicon carbon composite material includes 2 / g to 30m 2 / g, more preferably within the range of 4m 2 / g to 10m 2 / g of surface area in the range of 2m 2 / g, 30m 2 / g, 4m 2 / g and 10m 2 Appropriate boundaries of 100 g / g may also form part of the defined range. Thus, the first surface coating and / or the second surface coating may be effectively applied to the lithium silicon carbon composite material having an increased surface area due to its porous carbon support.

[0025] In another embodiment based on the lithium silicon carbon composite material, the lithium silicon carbon composite material comprises lithium. In addition, the first surface coating may also comprise lithium formed as a metal oxide. For example, the first surface coating may comprise a mixture of Al2O3, AlO(OH) and LiAlO2 or other lithium oxides, which may act as a channel for lithium ions during the reversible lithium insertion between the electrolyte and the lithium silicon carbon composite material. Therefore, the kinetics of lithium ions passing through the first surface coating and / or the second surface coating may be improved.

[0026] According to another aspect of the present invention, a method for manufacturing a surface-coated lithium silicon carbon composite material is provided. In the method step, a porous carbon support having micropores and mesopores is provided. In another step, a Li compound is introduced into the micropores and mesopores of the provided porous carbon support by a solution-based infiltration method. Then, the solvent in the solution-based infiltration method is removed to produce or form a microporous and mesoporous carbon support using the introduced Li compound. In addition, at least one additional compound containing Si and optionally at least one of Fe, Al, Ni, W and / or Ti is introduced into the micropores and mesopores of the porous carbon support by chemical vapor infiltration to form a lithium alloy carbon silicon composite material. The additional compound is preferably SiH4. At least one surface coating is at least partially applied to the surface area of ​​the lithium alloy carbon composite material. At least one surface coating contains silicon oxide, aluminum oxide or zirconium oxide or lithium oxide. Therefore, after applying at least one surface coating, a surface-coated lithium silicon carbon composite material is formed.

[0027] Aluminum or zirconium may remain in the material so that the surface-coated lithium silicon carbon composite material may also be formed as a surface-coated lithium alloy carbon silicon composite material.

[0028] By providing a surface coating comprising silicon oxide or aluminum oxide or zirconium oxide, the lithium silicon carbon composite material can be protected from undesirable chemical reactions (such as uncontrolled oxidation processes). In particular, when manufacturing a battery cell or an electrochemical energy storage device, an electrode comprising a surface-coated lithium silicon carbon composite material will provide improved chemical stability and reduce the possibility of undesirable chemical reactions due to at least a partial surface coating.

[0029] In order to introduce lithium into the lithium silicon carbon composite material, the lithium compound can be introduced into the micropores and mesopores of the provided porous carbon scaffold as LiAlH4 by a solution-based infiltration method. The solution can be removed using a vacuum and / or heating at a temperature, for example, above 100°C. After heating the resulting material and introducing SiH4 using a chemical vapor infiltration method at a temperature, for example, 450°C, byproducts such as CH4 and H2 can also evaporate. Therefore, only the Li-Al in the LiAlH4 can remain and form a Li-Al-Si alloy in the porous carbon scaffold.

[0030] In one embodiment, at least one surface coating of the surface region coating of the lithium silicon carbon composite is applied by a vapor deposition method. Thus, methods such as atomic layer deposition or molecular layer deposition can be performed to provide a surface coating with a controlled and uniform layer thickness.

[0031] In another embodiment, at least one surface coating of a lithium alloy carbon silicon composite material or a lithium silicon carbon composite material is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a processed compound surface on the surface area of ​​the lithium silicon carbon composite material; the processed compound surface is treated with moisture or oxygen or ozone to form at least one layer of a first surface coating. Such materials for forming processed compound surfaces are widely used and can therefore be provided in a cost-effective manner. For example, trimethylaluminum can be used to form a processed compound surface. By further heat treating the surface-coated lithium silicon carbon compound, the lithium from the lithium silicon carbon composite can react with aluminum oxide and / or zirconium oxide and form lithiated Al-O and Zr-O compounds (such as LiAlO2 and / or Li2ZrO3) as a surface coating.

[0032] In another embodiment, at least one surface coating of the surface region of the lithium silicon carbon composite material may alternatively have a lithium content. Thus, by providing lithium (e.g., LiAlO2) in addition to Al2O3, molecular pathways may be introduced for accelerating lithium ion exchange between the electrolyte and the lithium silicon carbon composite material of the electrode.

[0033] According to another embodiment, the surface coating of the surface region of the lithium silicon carbon composite material comprises a metal oxide from at least one of the elements B, Al, Si, Zr, Nb, W and / or Li. Thus, in the case of atomic layer deposition or molecular layer deposition, the metal oxide is used as a precursor. Alternative or additional precursors may be formed as ZrO2, TiO2, Al2O3, SiN x 、TaN x etc. and can be introduced by a mixing method. In addition, molecules such as Nb(OEt)5 or Li-N(SiMe3)2 can be introduced to precisely control the chemical composition of at least one surface coating. Thus, the method for making a surface-coated lithium silicon carbon composite material includes a variety of possible materials for adjusting the chemical and mechanical properties of the surface coating.

[0034] In another embodiment, during the formation of at least one surface coating of the surface coating of the lithium silicon carbon composite material, a temperature in the range of 25° C. to 550° C. is applied. Therefore, methods such as atomic or molecular layer thermal deposition or plasma enhanced atomic or molecular layer deposition are suitable for manufacturing the surface-coated lithium silicon carbon composite material.

[0035] According to another embodiment, treating the lithium silicon carbon composite material with a metal alkoxide or a metal amide or an alkyl metal compound to form a processed compound surface and treating the processed compound surface with moisture or oxygen or ozone is repeated at least once. Thus, it can be ensured that a uniform coating is formed on the surface area of ​​the lithium silicon carbon composite material without leaving any traces of the undesirable processed compound (e.g., AlCH3).

[0036] The manufacturing process can be accelerated if a temperature in the range of 25°C to 550°C is applied during the treatment of the processed compound with moisture, oxygen or ozone. Preferably, the manufacturing temperature of this step is in the range of 250°C to 450°C, more preferably in the range of 350° to 400°C.

[0037] According to another aspect of the present invention, a method for manufacturing at least one anode electrode is provided. In one step, a silicon-carbon composite mixture is mixed with at least one carbon. Preferably, the silicon-carbon composite mixture is formed as a lithium silicon-carbon composite mixture.

[0038] In another step, the silicon-carbon composite mixture is combined with at least one aqueous binder solution and / or at least one non-aqueous binder solution to form an electrode paste. In addition, the electrode paste is at least partially applied to at least one surface of a current collector. The current collector may be formed as a foil made of a conductive material.

[0039] In another step, the current collector applied with the electrode paste is dried at a temperature of 100° C. to 140° C. to form at least one anode electrode.

[0040] As adhesive, styrene-butadiene glue / carboxymethyl cellulose (CMC / SBR) blends, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA) can be used. In an alternative embodiment, the adhesive is formed as a fluoropolymer, such as polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), polyethylene tetrafluoroethylene (ETFE), polyvinyl fluoride (PVF), polyethylene trifluorochloroethylene (ECTFE), polyvinylidene fluoride (PCDF), polytrifluorochloroethylene (PCTFE), trifluoroethanol, or at least one of these materials and a combination of at least one other material. In another embodiment, the adhesive is a copolymer of polyimide or polyacrylic acid and styrene-butadiene. Other possible adhesives can be formed as methyl methacrylate or polyvinylidene fluoride.

[0041] The surface coating step may be applied after the electrode paste drying process, or the silicon-carbon composite may be provided in an already surface-coated form.

[0042] According to a preferred application, according to another aspect of the present invention, the method for manufacturing the anode electrode can also be performed based on a dry or semi-dry silicon-carbon composite mixture.

[0043] In a first step, a dry silicon-carbon composite mixture is provided, which is combined with a binder powder and contains graphite particles and / or carbon black particles. The binder powder may be formed as a PTFE powder.

[0044] Optionally, 5% to 10% ethylene carbonate may be added to the mixture.

[0045] Then, the silicon-carbon composite material mixture combined with the binder powder is at least partially applied to at least one surface of the conductor foil or the current collector by calendering. In another step, at least one surface coating is applied to the surface area of ​​the lithium silicon-carbon composite material to form a surface-coated lithium silicon-carbon composite material, wherein the at least one surface coating comprises aluminum oxide or zirconium oxide and at least partially covers the surface area of ​​the lithium silicon-carbon composite material.

[0046] The conductor foil to which the dried or semi-dried electrode paste is applied is then dried at a temperature of, for example, 100° C. to 140° C. to form at least one anode electrode.

[0047] In another aspect of the invention, an electrochemical energy storage device is provided, in particular in the form of a lithium ion battery or a lithium ion battery cell. The electrochemical energy storage device comprises at least one anode electrode of the invention, at least one cathode electrode, a separator between the cathode electrode and the anode electrode, and an electrolyte containing lithium ions. Preferably, the cathode electrode comprises a transition metal oxide. Preferably, the components of the electrochemical energy storage device are located inside a housing or a box (e.g., an aluminum bag).

[0048] By utilizing an anode electrode having a surface-coated silicon carbon material, the dry room environment requirements for manufacturing an electrochemical storage device can be reduced because the anode electrode surface is protected.

[0049] In another aspect, a use of a lithium silicon-carbon composite material in an anode electrode is disclosed, wherein the silicon-carbon composite comprises a porous carbon scaffold comprising micropores and mesopores and having a total pore volume of not less than 0.5 cm 3 / g; 30% to 70% silicon content; 2% to 20% (including 2% and 20%) lithium content; and comprising an at least partially applied first surface coating, the first surface coating forming a surface coating on the surface area of ​​the lithium silicon carbon composite, the surface coating comprising one or more elements of Li, B, Al, Si, P, Ti, Zr, Nb and / or W. The silicon content and the lithium content can be defined relative to the weight / mass or volume of the entire lithium silicon carbon composite.

[0050] In another embodiment, the surface coating on the silicon carbon composite has a thickness in a range of 0.1 nm to 0.1 μm.

[0051] In another embodiment, the surface coating on the lithium silicon carbon composite material comprises a metal oxide from at least one or more of the elements B, Al, Si, Zr, Nb, W and / or Li.

[0052] In another embodiment, the surface coating area of ​​at least one surface coating covers more than 50% of the surface area of ​​the lithium silicon carbon composite.

[0053] In another embodiment, the lithium silicon carbon composite comprises another surface coating or a second surface coating located on top of the first surface coating, such that the first surface coating and the second surface coating at least partially form a surface coating region.

[0054] In another embodiment, the other surface coating or the second surface coating is a carbon coating.

[0055] In another aspect, there is provided use of an anode electrode in an electrochemical energy storage device of the present invention.

[0056] The present disclosure will be described in more detail below based on the exemplary embodiments shown in the accompanying drawings: BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 A schematic diagram of a method for manufacturing a surface-coated lithium silicon carbon composite material according to one embodiment of the present invention is shown,

[0058] Figure 2 An exemplary electrochemical energy storage device having a fabricated electrode anode comprising a surface-coated lithium silicon carbon composite material and

[0059] Figure 3 An exemplary electrochemical energy storage device having a fabricated electrode anode including a surface-coated lithium silicon carbon composite material is shown according to another embodiment. DETAILED DESCRIPTION

[0060] In the drawings, the same reference numerals represent similar elements. The sizes and relative positions of the elements in the drawings are not necessarily drawn to scale, and some elements are enlarged and placed to improve the readability of the drawings. In addition, the specific shapes of the drawn elements are not intended to convey any information about the actual shape of the specific elements, but are only selected for ease of identification in the drawings.

[0061] Unless the context requires otherwise, in this specification and claims, the term "comprise" and variations thereof, such as "include" and "contain" should be interpreted in an open, inclusive sense, i.e., "including but not limited to". Unless otherwise stated, in this specification, any concentration range, percentage range, ratio range or integer range should be understood to include any integer value within the range, and, where appropriate, fractions thereof (such as one tenth and one hundredth of an integer). Unless otherwise stated, the terms "about" and "approximately" as used herein mean ±20%, ±10%, ±5% or ±1% of the range, value or structure. It should be understood that the terms "a" and "an" as used herein refer to "one or more" of the listed components. The use of alternatives (such as "or") should be understood to mean one, two or any combination of the alternatives.

[0062] References in this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment of the present disclosure. Therefore, the phrases "in one embodiment" or "in an embodiment" appearing in various places in this specification do not necessarily all refer to the same embodiment. Furthermore, in one or more embodiments, the particular features, structures, or characteristics may be combined in any suitable manner.

[0063] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs. As used in the specification and claims, the singular forms "a", "an", and "the" include plural references unless the context clearly dictates otherwise.

[0064] The term carbon part in the silicon-carbon composite material refers to a material or substance consisting of carbon or at least containing carbon. In this regard, the carbon material can include high purity, amorphous and crystalline materials. The carbon material can be activated carbon, pyrolyzed dry polymer gel, pyrolyzed polymer cryogel, pyrolyzed polymer xerogel, pyrolyzed polymer aerogel, activated dry polymer gel, activated polymer cryogel, activated polymer xerogel, activated polymer aerogel or a combination thereof. In another embodiment, carbon can be produced by pyrolysis of coconut shells or other organic wastes. In this regard, a polymer is a molecule comprising more than two repeating structural units. Porous carbon (also referred to as porous carbon material) has the advantages of being generally easy to produce, generally low in impurity content and large in pore volume. Therefore, porous carbon exhibits good electrical conductivity and high mechanical and chemical stability. In one embodiment, the carbon material has a high micropore volume ratio. Typically, porous carbon has a pore space, also referred to as a pore volume, wherein the pore space is a group of voids (pores) in the carbon that can be filled with a gas or fluid. In this regard, the properties and methods of making porous carbon are described in the prior art, such as U.S. Publication No. 2017 / 0015559, the entire disclosure of which is hereby incorporated by reference in its entirety for all purposes.

[0065] The Si portion of the silicon-carbon composite material may be pure silicon or a material composition containing silicon. For example, the Si portion may be at least one alloy. The alloy may be a silicon-titanium alloy (Si-Ti), a silicon-iron alloy (Si-Fe), or a silicon-nickel alloy (Si-Ni). In another embodiment, the Si portion may be composed of a P dopant, an As dopant, or an N dopant. The P dopant is typically a phosphorus dopant, the As dopant is typically an arsenic dopant, and the N dopant is typically a nitrogen dopant.

[0066] Figure 1 A schematic diagram of a method 1 for manufacturing a surface-coated lithium silicon carbon composite material 10 according to one embodiment of the present invention is shown.

[0067] In a first method step 2, a porous carbon support having micropores and mesopores is provided. The shapes and dimensions of the porous carbon support 20 and the lithium silicon carbon composite material 10 are shown for the purpose of illustrating method 1. The final shapes and dimensions of the materials used may vary depending on requirements.

[0068] In another method step 3, a lithium compound is introduced into the micropores and mesopores of the provided porous carbon support 20 by a solution-based infiltration method. Then, in another method step 4, the solvent in the solution-based infiltration method is removed to generate or form a microporous and mesoporous carbon support with the introduced lithium compound 21. Thus, the porous carbon support 20 is provided in a pre-lithiated form (e.g., Li-Al alloy).

[0069] Furthermore, in method step 5, at least one additional compound containing Si and optionally at least one of Fe, Al, Ni, W and / or Ti is introduced into the micropores and mesopores of the porous carbon support by chemical vapor infiltration to form the lithium alloy carbon silicon composite material 22. Preferably, SiH4 is used as the additional compound for the chemical vapor infiltration step.

[0070] In the following method steps 5 and 6, a surface coating 11 is provided on at least a portion of the surface area of ​​the lithium alloy carbon silicon composite material 22. At least one of the surface coatings 12 contains silicon oxide, aluminum oxide or zirconium oxide. The lithium alloy carbon silicon composite material 22 is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a processed compound layer (not shown). In the illustrated embodiment, the surface area of ​​the lithium alloy carbon silicon composite material 22 is covered with trimethylaluminum TMA. During the exposure of the surface area to trimethylaluminum, the trimethylaluminum dissociates and chemically adsorbs on the surface area of ​​the lithium alloy carbon silicon composite material 22, and any remaining gas phase trimethylaluminum can be easily removed.

[0071] The dissociative chemisorption of trimethylaluminum (TMA) results in a processed compound surface covered with AlCH3 molecules. The processed compound surface is treated with water H2O or oxygen O2 or ozone O3 to form at least one first surface coating 12.

[0072] The first surface coating 12 consists of Al2O3 molecules, since the treatment leads to a chemical reaction of CH3 on the surface of the processed compound. Such a coating can be provided by atomic layer thermal deposition, which also requires elevated temperatures, for example to 450°C.

[0073] In optional step 7, the first surface coating 12 can be treated with Li-N (SiMe3)2 and combined with heating to modify the first surface coating 12 into a modified first surface coating 13, so that it contains Li in the form of LiAlO2 in addition to Al2O3 molecules. Such lithium-containing molecules can increase the kinetics of Li ions passing through the modified first surface coating 13.

[0074] In a further step 8, a second surface coating 14 can be applied on top of the first surface coating 13, which was previously modified so that it contains LiAlO2 and Al2O3 molecules. In the example shown, the second surface coating 14 consists of carbon C.

[0075] The first surface coating 13 and the second surface coating 14 constitute a surface coating 11 of a lithium silicon carbon composite material, so that after application of the surface coating 11 a surface-coated lithium silicon carbon composite material 10 is formed, which in the illustrated example is a lithium alloy silicon carbon silicon composite material.

[0076] Figure 2 A cross-sectional view of an exemplary electrochemical energy storage device 100 is shown, wherein the electrochemical energy storage device 100 has an electrode anode 110, wherein the electrode anode 110 includes Figure 1 The surface-coated lithium silicon carbon composite material 10 is manufactured by the method shown.

[0077] The electrochemical energy storage device 100 is formed as a lithium-ion battery cell. The electrochemical energy storage device 100 comprises at least one anode electrode 110, at least one cathode electrode 120 and a separator 130 arranged between the cathode electrode 120 and the anode electrode 110. The cathode electrode preferably contains a transition metal oxide.

[0078] In addition, an electrolyte 140 containing lithium ions is also provided in the battery case 150 of the electrochemical energy storage device 100. The electrochemical energy storage device 100 may be formed as a pouch-shaped lithium ion battery. Therefore, the battery case 150 may be formed as an aluminum bag. The anode electrode 110, the cathode electrode 120 and the separator 130 are also arranged in the battery case 150.

[0079] It is worth noting that Figure 2 A simplified cross-sectional view is shown. Anode electrode 110, cathode electrode 120 and separator 130 are typically formed in multiple layers that are rolled or folded to optimize packaging and increase the possible surface area for electrolyte 140. In the embodiment shown, only one layer of the components is visible for illustration purposes.

[0080] Both sides of the anode electrode 110 are coated with a surface-coated lithium alloy lithium silicon-carbon composite material 10 , and the surface coating 11 of the surface-coated lithium silicon-carbon composite material 10 is applied on the surface area of ​​the lithium silicon-carbon composite material 10 that is not in contact with the current collector 111 of the anode electrode 110 .

[0081] By utilizing an anode electrode 110 having a surface-coated silicon-carbon material 10, the requirements for a dry room environment in manufacturing an electrochemical energy storage device 100 can be reduced. In particular, during the filling of the electrolyte 140 into the battery housing 150, chemical interactions of the electrode anode with contaminants can be reduced or prevented due to surface protection by the surface coating 11.

[0082] Figure 3 Another exemplary electrochemical energy storage device 100 is shown. The electrochemical energy storage device 100 includes an electrode anode 110 having a surface-coated lithium silicon carbon composite material 10. Figure 2In contrast to the embodiment shown, the surface coating 11 of the lithium silicon carbon composite material 10 is partially applied to the surface region of the lithium silicon carbon composite material 10 , so that parts of the surface region of the lithium silicon carbon composite material 10 remain free of the surface coating 11 .

Claims

1. A lithium silicon carbon composite material (10), formed as a surface-coated lithium silicon carbon composite material, the lithium silicon carbon composite material (10) comprising: A porous carbon support (20) comprising micropores and mesopores and having a total pore volume of not less than 0.5 cm 3 / g; - a silicon content of 30% to 70%, inclusive; - a lithium content of 2% to 20%, inclusive; as well as - an at least partially applied first surface coating (12), which forms a surface coating (11) on the surface area of ​​the lithium silicon carbon composite, and the first surface coating (12) contains one or more elements of Li, B, Al, Si, P, Ti, Zr, Nb and / or W.

2. The material according to claim 1, wherein The at least partially applied first surface coating (12, 13) has a thickness in the range of 0.1 nm to 1 μm.

3. The material according to claim 1 or 2, wherein the first surface coating (12, 13) comprises a metal oxide formed from at least one of the elements Li, B, Al, Si, P, Ti, Zr, Nb and / or W.

4. The material according to any one of claims 1 to 3, wherein at least 50% or more of the surface area of ​​the lithium silicon carbon composite material (10) is covered by the surface coating (11).

5. The material according to any one of claims 1 to 4, wherein the surface coating (11) of the lithium silicon carbon composite material (10) comprises a second surface coating (14).

6. The material according to claim 5, wherein the second surface coating (14) is formed as a carbon coating.

7. The material according to any one of claims 1 to 6, wherein the surface area of ​​the lithium silicon carbon composite material (10) is within 2 m 2 / g to 30m 2 / g range, especially in the 4m 2 / g to 10m 2 / g range.

8. The material according to any one of claims 1 to 7, wherein the first surface coating (13) comprises lithium in the form of LiAlO2 or Li2ZrO3 molecules.

9. A method (1) for producing a surface-coated lithium silicon carbon composite material (10) as claimed in any one of claims 1 to 8, wherein - providing a porous carbon scaffold (20) having micropores and mesopores, - introducing lithium compounds into the micropores and mesopores of the provided porous carbon scaffold (20) by a solution-based infiltration method, - removing the solvent to produce microporous and mesoporous carbon scaffolds with the introduced lithium compound (21), - introducing Si and at least one additional compound into the micropores and mesopores of the porous carbon support by chemical vapor infiltration to form a lithium alloy carbon silicon composite material (22), wherein the at least one additional compound comprises Fe, Al, Ni, W and / or Ti, - at least one surface coating (12, 13) is at least partially applied on the surface area of ​​the lithium alloy carbon silicon composite material (22), wherein the at least one surface coating (12, 13) contains silicon oxide, aluminum oxide or zirconium oxide, thereby forming a surface-coated lithium silicon carbon composite material (10).

10. The method according to claim 9, wherein LiAlH4 as the lithium compound is introduced into the micropores and mesopores of the provided porous carbon support (20) by a solution-based infiltration method.

11. The method according to claim 9 or 10, wherein the at least one surface coating (12, 13) is at least partially applied to the surface area of ​​the lithium silicon carbon composite material (10) by a vapor deposition method.

12. A method according to any one of claims 9 to 11, wherein the lithium alloy carbon silicon composite material (22) is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a processed compound layer on the surface area; and wherein the processed compound layer on the surface area is treated with moisture or oxygen or ozone to form at least one surface coating (12).

13. A method according to any one of claims 9 to 12, wherein a surface coating (11) of a surface region of the lithium silicon carbon composite material (10) contains lithium in at least one surface coating (13) and / or lithium as part of the lithium silicon carbon composite material (10).

14. A method according to any one of claims 9 to 13, wherein the surface coating (11) of the surface area of ​​the lithium silicon carbon composite material (10) contains at least one metal oxide formed by at least one of the elements Li, Al, Si, Zr, Nb and / or W.

15. The method according to any one of claims 9 to 14, wherein the at least one surface coating (12, 13) is applied to the surface area of ​​the lithium silicon carbon composite material (10) at a temperature in the range of 25°C to 550°C.

16. The method according to claim 12, wherein treating the lithium alloy carbon silicon composite material (22) with metal alkoxide or metal amide or alkyl metal compound to form a processed compound layer and treating the processed compound layer with moisture or oxygen or ozone are repeated at least once.

17. The method according to any one of claims 12 or 16, wherein treating the processed compound layer with moisture or oxygen or ozone is performed at a temperature in the range of 25°C to 450°C.

18. An anode electrode (110), comprising a current collector (111) and a surface-coated lithium silicon-carbon composite material (10) according to any one of claims 1 to 8, wherein the surface-coated lithium silicon-carbon composite material is arranged on at least one side of the current collector.

19. The anode electrode according to claim 18, wherein The surface area of ​​the lithium silicon carbon composite material (10) not in contact with the current collector (111) is at least partially covered with a surface coating (11), and the surface coating (11) has a layer thickness in the range of 0.1 nm to 1 μm.

20. A method for manufacturing at least one anode electrode (110) according to claims 18 and 19, wherein - providing a silicon-carbon composite mixture, in particular a lithium silicon-carbon composite mixture, comprising at least one carbon compound, - combining the silicon-carbon composite mixture with the carbon compound with an aqueous binder solution and / or a non-aqueous binder solution to form an electrode paste, - applying the electrode paste to a current collector, such as a conductor foil, - Drying the current collector to which the electrode paste is applied at a temperature of 100° C. to 140° C., thereby forming at least one anode electrode.

21. Method for producing at least one anode electrode (110) according to claim 17, wherein - providing a dry or semi-dry silicon-carbon composite mixture, in particular a lithium silicon-carbon composite mixture, having at least one carbon; wherein the mixture is combined with a binder powder and contains graphite particles and / or carbon black particles; - applying the silicon-carbon composite mixture combined with the binder powder at least partially on at least one surface of a current collector formed as a conductor foil (111) by calendering; - drying the conductor foil (111) with the applied mixture at a temperature of 100°C to 140°C to form at least one anode electrode (110).

22. An electrochemical energy storage device (100), in particular in the form of a lithium-ion battery, comprising: - at least one anode electrode (110) according to any one of claims 18 and 19; - at least one cathode electrode (120) comprising a transition metal oxide; - a separator (130) disposed between the cathode electrode (120) and the anode electrode (110); and - an electrolyte (140) comprising lithium ions.

23. The material according to any one of claims 1 to 8, wherein the first surface coating (12, 13) comprises a metal oxide formed from Li, in particular comprises a metal oxide formed from Li in addition to Al2O3.

Citation Information

Patent Citations

  • Novel methods for sol-gel polymerization in absence of solvent and creation of tunable carbon structure from same

    US20170015559A1